Outcomes of 188 Proximal Humeral Fractures Treated with a Dedicated External Fixator with Follow-up Ranging from 2 to 12 Years. (18th September 2019) - Blonna, Davide; Assom, Marco; Bellato, Enrico; Pisanu, Gabriele; Greco, Valentina; Marmotti, Antonio; Rossi, Roberto
Abstract : Background: The treatment of a displaced proximal humeral fracture is still a matter of controversy. Minimally invasive techniques are considered promising options. The purpose of this study was to report outcomes at medium to long-term follow-up after surgical treatment with pins stabilized with an external fixator. Methods: A total of 235 patients (average age, 64 years [95% confidence interval (CI), 62 to 65 years]) were treated with closed or open reduction and fixation with pins stabilized by an external fixator specifically designed for proximal humeral fractures. The pins were inserted using a "pins-crossing-fracture" or a "pins-bridging-fracture" technique. One hundred and eighty-eight patients had a minimum radiographic and clinical follow-up of 2 years. Outcomes were assessed using the Oxford Shoulder Score (OSS), the subjective shoulder value (SSV), a visual analog scale (VAS) for pain, and, for 155 patients, the Constant score. Results: Eighty-one (43%) of the 188 patients had a 2-part fracture, 60 (32%) had a 3-part fracture, and 47 (25%) had a 4-part fracture. The reduction was performed with percutaneous maneuvers in 120 shoulders or a deltopectoral approach, in 68. The external fixator was applied using a "pins-crossing-fracture" technique in 133 shoulders and using a "pins-bridging-fracture" technique in 55. At last follow-up, mean clinical scores were as follows: OSS, 42.6 (95% CI, 42 to 44); SSV, 85.5 (95% CI, 83 to 88); and VAS for pain, 1 (95% CI, 0.7 to 1.2). The complication rate at 3 months was 16% (37 of 235). The most frequent complication was pin-track infection (19 of 235, 8%). A total of 50 patients had ≥1 complication (50 of 188, 27%) and 6 (3%) underwent revision surgery. More complications were observed with the "pins-crossing-fracture" technique. Conclusions: In our experience, the use of the external fixator has been a valuable option in the treatment of proximal humeral fractures. The complication and revision rates were acceptable. Most of the complications encountered were manageable without revision surgery. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.